2005
DOI: 10.1111/j.0105-1873.2005.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

The complex problem of sensitive skin

Abstract: There exists within the population subsets of individuals who display heightened skin reactivity to materials the majority find tolerable. In a series of investigations, we have examined interrelationships between many of the endpoints associated with the term 'sensitive skin'. In the most recent work, 58 volunteers were treated with 10% lactic acid, 50% ethanol, 0.5% menthol and 1.0% capsaicin on the nasolabial fold, unoccluded, with sensory reactions recorded at 2.5 min, 5 min and 8 min after application. Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
114
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 13 publications
0
114
1
2
Order By: Relevance
“…However, 66.7% of nonsensitive subjects also experience this reaction. Moreover, several studies have shown that sensitivity to one substance seems not to predict sensitivity to another [28,35,39], questioning the validity of the LAST as a reliable diagnostic test for sensitive skin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 66.7% of nonsensitive subjects also experience this reaction. Moreover, several studies have shown that sensitivity to one substance seems not to predict sensitivity to another [28,35,39], questioning the validity of the LAST as a reliable diagnostic test for sensitive skin.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the assessment of erythema in skin irritation has been widely investigated, either by visual assessment [28,37,41,59,60] or by quantitative methods such as tristimulus reflectance colorimetry (a* value) [20,50,51,52], reflectance spectrophotometry (erythema index) [38,53,59] or laser Doppler flowmetry (cutaneous blood flow) [20,41,48,50,51,53,61]. Increased vascular reactivity has been emphasized in the literature as a key player in sensitive skin pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, SS is a functional term used by individuals who show reduced tolerance to frequent or prolonged use of cosmetics and toiletries with sensitive reactions such as intolerable burning or itching sensation. 1,2 Tests for diagnosing SS include subjective testing, which involves determining the degree of skin irritation by applying stimulants and evaluating the subject's opinion, and objective testing, which involves visual or mechanical observation. However, there is no standardized method for diagnosing SS.…”
Section: Introductionmentioning
confidence: 99%
“…Patients usually report an itching, stinging and burning sensation. Often it is not possible to identify a single cause for the symptoms, since they are not specific [2,7] .…”
Section: Introductionmentioning
confidence: 99%